2017
DOI: 10.1785/0220160153
|View full text |Cite
|
Sign up to set email alerts
|

Are Ground‐Motion Models Derived from Natural Events Applicable to the Estimation of Expected Motions for Induced Earthquakes?

Abstract: Natural earthquakes in western North America can be reasonable proxies for induced earthquakes in central and eastern North America because of the opposing effects that source depth and tectonic setting have on the stress parameter that scales high-frequency ground-motion amplitudes. It is critical that ground-motion prediction equations selected as induced-event proxies have appropriate near-distance scaling behavior for small-to-moderate shallow events. In this article, we describe the conditions under which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Because ground motion intensities at high frequencies are controlled primarily by stress drop (Baltay et al, , ; Boore, ; Douglas & Edwards, ; Yenier & Atkinson, ), its characterization is of fundamental interest to studies that aim to develop ground motion prediction equations for induced events (Atkinson & Assatourians, ; Atkinson et al, ; Yenier et al, ). In this study, we observe quantifiable time‐dependent and depth‐dependent variations in stress drop, both of which are in accord with the conclusions of Yenier et al () and Atkinson and Assatourians () for ground motions of recent seismicity in Oklahoma. This consistency suggests that the results we present could potentially serve as a basis for future studies focused on quantifying the influence that spatiotemporal and depth‐dependent variations in earthquake source properties may have on the observed ground motion amplitudes of induced earthquakes in the central United States.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because ground motion intensities at high frequencies are controlled primarily by stress drop (Baltay et al, , ; Boore, ; Douglas & Edwards, ; Yenier & Atkinson, ), its characterization is of fundamental interest to studies that aim to develop ground motion prediction equations for induced events (Atkinson & Assatourians, ; Atkinson et al, ; Yenier et al, ). In this study, we observe quantifiable time‐dependent and depth‐dependent variations in stress drop, both of which are in accord with the conclusions of Yenier et al () and Atkinson and Assatourians () for ground motions of recent seismicity in Oklahoma. This consistency suggests that the results we present could potentially serve as a basis for future studies focused on quantifying the influence that spatiotemporal and depth‐dependent variations in earthquake source properties may have on the observed ground motion amplitudes of induced earthquakes in the central United States.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific consensus has attributed much of the elevated seismicity rate to anthropogenic activity and in particular to the injection of wastewater from the oil production process into the Arbuckle Group that is stratigraphically above the granitic basement (e.g., Buchanan, 2015;Ellsworth, 2013;Ellsworth et al, 2015;Rubinstein & Mahani, 2015;Walsh & Zoback, 2015;Yeck et al, 2017). The abrupt increase in seismic hazard within this region (Petersen et al, 2016(Petersen et al, , 2017 has spurred numerous observational studies focused on connections between fluid injection and seismicity rates (Barbour et al, 2017;Choy et al, 2016;Goebel, 2015;Keranen et al, 2013Keranen et al, , 2014Weingarten et al, 2015), the source properties of a subset of the larger events (Boyd et al, 2017;Choy et al, 2016;Cramer, 2017;Sumy et al, 2017;Walter et al, 2017), and observed ground motion amplitudes (Atkinson & Assatourians, 2017;Atkinson et al, 2016;Hough, 2014;Yenier et al, 2017). Although these studies have rapidly advanced scientific understanding of these earthquakes, there is still much that remains unanswered, and the nonstationary nature of the seismicity warrants continued monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…We also did not evaluate the influence of focal depth on the observed differences in amplitudes. Yenier and Atkinson (2015) and Atkinson and Assatourians (2017) note that earthquake stress drops increase with increasing depth and have attributed the difference in tectonic-versus-induced ground-motion amplitudes to this factor. Development of more detailed site information at seismic stations in the CEUS, and development of a validated site amplification model, would help resolve some of the above uncertainties.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the induced earthquakes occurred in the central United States, whereas the tectonic earthquakes occurred primarily in the eastern United States, so the differences between induced or tectonic data sets could be due to regional difference in geology as well as the origin. Additionally, the differences may also be due to the dependence of earthquake source parameters on focal depth, as shown by Yenier and Atkinson (2015) and Atkinson and Assatourians (2017).…”
Section: Observations For Other Intensity Measuresmentioning
confidence: 99%
“…More recently, specific studies on GMPEs for induced seismicity have been proposed for areas where large database of waveforms are available, such as Basel, Geysers, Soultz [Douglas et al, 2013], or Groningen [Bommer et al, 2016]. Recent studies suggest that, for the same focal depth and tectonic setting, the ground motions for natural and induced events appear to be similar [Atkinson and Assatourians, 2017]. However, the verification of GMPEs and their application in the field of induced seismicity is still a new and challenging topic of research.…”
Section: 1002/2016rg000542mentioning
confidence: 99%